Evaluation of Physician Assistants’ Self-Reported Attitudes and Behaviors After Completion of a Hospital-Wide Multidisciplinary Communication Skills Training Workshop - Minna Saslaw MD; Steven Kaplan MD; Martina Pavlicova PhD; Marcy Rosenbaum PhD; Dana R. Sirota MD, MPH (Journal of Patient Experience, 2022)
Physician's assistants (PA) are an integral part of hospital teams. To the best of our knowledge, this is the first study to examine the effects of a multidisciplinary hospital-wide communication skills training (CST) workshop on PAs. From November 2017 to November 2019, all participants in the CST workshop were sent a web-based retrospective pre-post survey to measure self-reported attitudes and behaviors related to communicating with patients, CST, and specific skills taught. PA responses were analyzed alone and were compared to non-PAs. Non-PAs were physicians and 1 nurse practitioner. In total, 258 PA and 333 non-PA participants were surveyed for an overall response rate of 25%. Among PAs, in 9 out of 10 domains measured, there was a significant change in self-reported attitudes and behaviors toward communicating with patients, CST, and skills taught ( P  < .05). Similar to other providers, PAs experienced positive changes in these self-reported attitudes and behaviors after CST, however, there were some significant differences found when comparing PAs and non-PAs in the covariate analysis.